2015
DOI: 10.1002/srin.201400503
|View full text |Cite
|
Sign up to set email alerts
|

New Developments in Martensitic Stainless Steels Containing C + N

Abstract: The use of nitrogen in martensitic stainless steels is limited by its solubility. Nitrogen solubility can be increased by alloying with elements such as Cr, Mn, and Mo and the use of pressure, such as in Pressurized ElectroSlag Remelting (PESR). Furthermore, the joint addition of C þ N increases their solubility. Solid-state nitriding can be used for case hardening or N-enrichment of steel powders before sintering. However, the resulting stabilization of austenite can be a drawback for martensitic steels. Besi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…While after austenitzing at 1050 °C E pit is reached at 284 ± 75 mV SCE , austenitizing at 1150 °C shifts E pit to much higher values of 438 ± 15 mV SCE . This tendency is in good agreement with several previous studies and can be explained by the higher amounts of Cr, Mo, and N in the matrix. Due to the dissolution of carbides respectively carbonitrides, less Cr‐depleted zones exist, which impair the resistance against pitting corrosion significantly.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…While after austenitzing at 1050 °C E pit is reached at 284 ± 75 mV SCE , austenitizing at 1150 °C shifts E pit to much higher values of 438 ± 15 mV SCE . This tendency is in good agreement with several previous studies and can be explained by the higher amounts of Cr, Mo, and N in the matrix. Due to the dissolution of carbides respectively carbonitrides, less Cr‐depleted zones exist, which impair the resistance against pitting corrosion significantly.…”
Section: Resultssupporting
confidence: 93%
“…To consider the influence of nitrogen on the austenite stability, Andrews’ equation has been modified by adding the composition of N to that of C as both are presumed to pose similar effect on the hardenability as suggested by Krasokha and Berns . This modified formula was also used within the studies of Seifert et al on C + N alloyed MSS containing 15 wt% Cr and 1 wt% Mo . Thereby, Seifert and Theisen found that Equation gives the best approximation to experimentally determined M s ‐temperature values compared with those obtained by other empirical formulae such as the Steven and Haynes and Barbier equation.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, commercial DSSs including UNS S32101, UNS S32304, UNS S32205, and UNS S32750, contain 0.1-0.3 wt% N. However, alloying C to DSSs has rarely been attempted, although C is found to be beneficial to performances of γ-SSs, similarly to N. Generally, C content was carefully controlled to be less than 0.03 wt% for commercial DSSs, because DSSs can provide more sites to Cr 23 C 6 precipitations such as phase boundaries than the γ-SS [19,35,36]. But as long as C remains in solid solution state, it is expected to take advantages of the alloying C in promoting the physico-chemical properties of DSSs, the possibility of which was supported by the previous studies on C-bearing γ-SSs [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 98%
“…The beneficial effects of alloying nitrogen (N) [1][2][3][4][5][6][7][8][9] and carbon (C) [10][11][12][13][14][15][16][17][18][19][20] on mechanical properties and resistance to the localized corrosion of austenite stainless steels (γ-SSs) are widely investigated, and their mechanistic roles in the performance improvements are well established. N and C are economical and strong γ formers, thus they can be used in the γ-SS in replacement of Ni.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation